Janus Kinase 3 Deficiency Promotes Vascular Reendothelialization—Brief Report. Issue 6 (29th April 2021) - Wang, Yung-Chun; Cai, Dunpeng; Cui, Xiao-Bing; Chuang, Ya-Hui; Fay, William P.; Chen, Shi-You
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: The objective of this study is to determine the role of JAK3 (Janus kinase 3) in reendothelialization after vascular injury. Methods and Results: By using mouse carotid artery wire injury and rat balloon injury model, we found that JAK3 regulates reendothelialization and endothelial cell proliferation after vascular injury. JAK3 and phospho-JAK3 levels were increased in neointimal smooth muscle cells in response to vascular injury in mice. JAK3 deficiency dramatically attenuated the injury-induced intimal hyperplasia in carotid arteries of both male and female mice. Importantly, JAK3 deficiency caused an increased rate of reendothelialization following mechanical injury. Likewise, knockdown of JAK3 in medial smooth muscle cells elicited an accelerated reendothelialization with reduced intimal hyperplasia following balloon injury in rat carotid arteries. Interestingly, knockdown of JAK3 restored the expression of smooth muscle cell contractile protein smooth muscle α-actin in injury-induced intimal smooth muscle cells while increased the proliferating endothelial cells in the intima area. Conclusions: Our results demonstrate a novel role of JAK3 in the regeneration of endothelium after vascular injury, which may provide a new strategy to enhance reendothelialization while suppressing neointimal formation for effective vascular repair from injury.